2016
DOI: 10.1111/jog.12930
|View full text |Cite
|
Sign up to set email alerts
|

Post‐partum hypoglycemia and hypothermia as first manifestations of lymphocytic adenohypophysitis: A case report

Abstract: Lymphocytic adenohypophysitis is a very rare autoimmune disease characterized by an anterior pituitary infiltration of lymphocytes that cause various symptoms, such as headache, visual disturbance, and hypopituitarism. Lymphocytic adenohypophysitis is more common in women and has a remarkable association with the perinatal period. Recently, we experienced a case of lymphocytic adenohypophysitis shortly after delivery. A 37-year-old primiparous woman delivered her baby at 38 weeks' gestation. The next morning, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…• The second case described a complex association of post-partum hypothermia, hypoglicemia, hypoadrenalism and hypothyroidism, accompanied by characteristic findings on MRI. Following these results, the authors suggested that practitioners should keep in mind the possibility of LYH in any pregnant women with symptoms of hypoglicemia and hypothermia after delivery [132]. • The rupture of Rathke' cleft cyst may cause lymphocytic-infundibulo-neurohypophysitis.…”
Section: Autoimmune Hypophysitis Under False Pretencesmentioning
confidence: 99%
“…• The second case described a complex association of post-partum hypothermia, hypoglicemia, hypoadrenalism and hypothyroidism, accompanied by characteristic findings on MRI. Following these results, the authors suggested that practitioners should keep in mind the possibility of LYH in any pregnant women with symptoms of hypoglicemia and hypothermia after delivery [132]. • The rupture of Rathke' cleft cyst may cause lymphocytic-infundibulo-neurohypophysitis.…”
Section: Autoimmune Hypophysitis Under False Pretencesmentioning
confidence: 99%
“…Hypophyseal malfunction may be associated with late pregnancy or the early postpartum period, as the stress of pregnancy and delivery can at times unmask an underlying condition. Lymphocytic adenohypophysitis is one type of hypophyseal disorder that has been uncovered in this fashion and may cause symptoms including hypothermia with presentations similar to sellar compression, diabetes insipidus, hypopituitarism, hypoglycemia, or hyperprolactinemia [13]. Laboratory evaluation and head imaging should be considered to assess for signs of lymphocytic adenohypophysitis.…”
Section: Discussionmentioning
confidence: 99%